Aktualnost raziskovanja in proučevanja migrantskega dela žensk v kontekstu aleksandrinstva - Milharčič-Hladnik, Mirjam (Etnolog. Nova vrsta (Ljubljana), 2013)
The article describes the context of research into women's migrations and carework as a contemporary phenomenon of the developed world, where it was supposed to have disappeared long ago. It places the book about the ŽAlexandrian womenŽ by Daša Koprivec in a wider European and global research trend, presenting historical and contemporary forms of women's paid care work.Work and the migration of women connected to it have always been embeddedin normative, socially prescribed gender roles, and as a result in thenational imagination. As the text shows, the (past) migration of women to Alexandria is therefore once more an important social topic in Slovenia. Equally important are the subjective experiences of the women migrants and their descendants, which are now finally heard thanks to researches and books like the present one by Daša Koprivec.
Keywords: Slovenian emigrants; slovenske izseljenke; aleksandrinke; Alexandrians; woman; national imagination; ženske; human migration; migracije; women (migration); care work; Egipt; Egypt